Design of Arbitrary Image Slicer in Execution of Steganography - Balasubramani, A; Subba Rao, Chdv (International Journal of Computer Sciences and Engineering, 2025)
A new coding technique is projected in this paper. Steganography and visual Cryptography is employed to achieve the security. The secret colour image is hidden behind a canopy image. The steganographic image is currently sliced into multiple slices and transmitted in an open system setting. At the receiver side, the received slices are organised in such a way that to come up with the original image, that has the secret colour image hidden in it. This can be done by Visual Cryptography. Currently Steganography is employed on this image to get the secret image.